Pre-slaughter conditions influence skatole and androstenone in adipose tissue of boars. (January 2015) - Wesoly, Raffael; Jungbluth, Ina; Stefanski, Volker; Weiler, Ulrike
Abstract: Boar taint in carcasses may vary between farms and abattoirs, although the underlying mechanisms are not yet fully understood. In the present study, 169 boars from three farms were split into two groups and slaughtered at two abattoirs. Duration of transport and the time between arrival at the abattoir and unloading (pre-unloading time) were recorded. During slaughter, blood, feces, and urine were collected to measure testosterone and cortisol levels. Carcasses were classified according to the number of skin lesions, and fat samples were taken to determine skatole, indole and androstenone levels. Androstenone in fat and testosterone in blood, feces, and urine were mainly influenced by the duration of transport. Skatole and indole concentrations were increased by both pre-unloading time and duration of transport, but were also related to skin lesions. Thus it is concluded that androstenone and skatole concentrations in fat are significantly modified by pre-slaughter conditions. Highlights: Boar taint compounds in fat are influenced by pre-slaughter treatment of boars. Androstenone levels increase with the duration of transport to the abattoir. Skatole levels increase with the time spent on the vehicle after arrival. Fighting as indicated by skin injuries seems to influence skatole levels in fat.